2021
DOI: 10.3168/jds.2021-20127
|View full text |Cite
|
Sign up to set email alerts
|

Pain in the weeks following surgical and rubber ring castration in dairy calves

Abstract: Many male dairy calves are castrated when reared for beef production, but for dairy breeds the assessment of the longer-lasting pain associated with this procedure has received little scientific attention. In this study we assessed 2 methods: surgical (n = 10 calves) and rubber ring (n = 11). All calves were castrated at 28 d of age using multimodal pain control. During the 8 wk that followed, we recorded wound healing, local inflammation, body weight, milk and calf starter intake, lying time, and wound-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… Marti et al (2017) reported a lower weight gain over 68 d for surgically castrated calves compared with control and band calves, despite more intense and longer swelling for band castration calves. In a study with methods most comparable to ours (use of sedative, local anesthesia, and analgesia in Holstein calves <1 mo old), calves castrated with rubber rings took longer to heal, had more inflammation, gained less weight, spent less time lying, and exhibited more lesion lickings than surgically castrated calves ( Nogues et al, 2021 ).…”
mentioning
confidence: 59%
“… Marti et al (2017) reported a lower weight gain over 68 d for surgically castrated calves compared with control and band calves, despite more intense and longer swelling for band castration calves. In a study with methods most comparable to ours (use of sedative, local anesthesia, and analgesia in Holstein calves <1 mo old), calves castrated with rubber rings took longer to heal, had more inflammation, gained less weight, spent less time lying, and exhibited more lesion lickings than surgically castrated calves ( Nogues et al, 2021 ).…”
mentioning
confidence: 59%
“…When using a rubber band for castration, a combination of local anesthetic and NSAID can control pain over a short period after castration, yielding no formation of negative memory associated with the procedure in the 96 h after completion [ 32 ]. However, in the weeks following rubber band application, calves exhibit lower weight gains, starter intake, and lying time likely associated with a protracted pain response [ 12 ], suggesting that NSAID re-administration would be required to maintain efficacy over the duration of the elastration procedure. LLBs, on the other hand, were designed to address both acute and chronic discomfort by delivering lidocaine rapidly and for a prolonged duration.…”
Section: Discussionmentioning
confidence: 99%
“…Although this method initially leads to fewer obvious signs of pain [ 9 ], the pain related to band castration is chronic as the wound-healing process can last for weeks [ 10 , 11 ]. Furthermore, when compared to the use of surgical castration, dairy calves castrated with a rubber ring gained less weight and spent less time lying down over the 8-week study period [ 12 ]. This highlights the need for better methods to control the long-term pain associated with this castration method.…”
Section: Introductionmentioning
confidence: 99%
“…These results might be associated with a similar inflammatory and painful response in all bulls, showing that IRT can be an adjuvant to monitor the healing period and manage pain, an important sign that also must be considered [ 90 ]. In longer-lasting pain procedures such as rubber ring castration, usually performed in domestic animals, Nogues et al [ 91 ] evaluated wound healing and inflammation in dairy calves after surgical or rubber ring castration. Rubber-ring-castrated animals did not fully heal within the eight evaluation weeks and, according to IRT, the thermal surface response around the lesion was 1.7 ± 0.35 °C higher than the surgical group.…”
Section: Infrared Thermography Used To Monitor Healing and Surgical W...mentioning
confidence: 99%